FACTORS INFLUENCING THE ORGANIZATIONAL PERFORMANCE IN SMALL SCALE INDUSTRIES IN SRI LANKA - Pushpanathan, A. (University of Colombo, 2008)
The research on factors influencing on organizational performance in small scale entrepreneurs in SriLanka is limited. Some researches were based on the factors such as environmental, economic, socio and cultural, affecting the challenges of small scale industries in Sri Lanka. But these researches did not consider the organizational performance as dependent variable. The present study is to explore the factors influencing on the organizational performance in small scale industries in Sri Lanka. The main objective of the study is to analysis the relationship between factors- personal factors, and environmental factors- and the organizational performance in small scale industries in Sri Lanka. The personal factors- age of owner, education of owner, and experience of owner- and environmental factors- firm size, family ownership, technology, firm development stage – are considered as independent variables, and profitability is considered as dependent variables. Data were collected from the small scale industries those who are registered under the Chamber of Commerce and Industry in Sri Lanka. The sample size is 220.The questionnaire was issued to owner of small scale industries. Structural equation model with path analysis (AMOS) is used to measure the relationship between personal and environmental factors and organizational performance. The fact the model partially supports to personal and environmental factors and firm performance.
Keywords: Personal factors; Environmental factors; Performance; Small Scale Industries